Stereoselective total synthesis of (+/-)-pleurospiroketals A and B - Thorat, Sagar S.; Krishna, Gamidi Rama; Kontham, Ravindar (Journal of Organic Chemistry, 2021)
A full account of our efforts toward the stereoselective total synthesis of sesquiterpenoid-derived natural products (+/-)-pleurospiroketals A and B is described. Commercially available 3-methyl-2-cyclohexenone and 2,2-dimethyloxirane were used as key building blocks, and the substrate-controlled stereoselection was exploited to access the entire stereochemistry of these natural products. Initially, a planned synthetic route involving a [6,5]-bicyclic lactone intermediate was found to be insurmountable, and the later strategy comprising OsO4-NMO-mediated dihydroxylation of 3-methyl-2-cyclohexenone, followed by Luche reduction, Eschenmoser methylenation, and Bronsted acid-induced spiroketalization steps, was ultimately identified as the reliable strategy.